Deciphering the Relationship Between Janus Kinase -2 (Jak-2) Mutation and Thrombocytopenia - Sanaullah, Shawaiz; Dayan, Ibrahim; Hashmi, Abdal Ali Qureshi; Anjum, Nida; Ejaz, Mariam; Zhaira, Ismat; Zhaira, Dua (Biological and Clinical Sciences Research Journal, 2025)
Hematological parameters, including white blood cells (WBCs), haemoglobin (HB), hematocrit (HCT), and platelet (PLT) levels, play a crucial role in assessing overall health and disease conditions. Understanding their relationships with various influencing factors is essential for refining diagnostic and prognostic evaluations. Objective: This study aimed to explore the relationships between various haematological parameters, including white blood cells (WBCs), haemoglobin (HB), hematocrit (HCT), and platelet (PLT) levels, and their respective influencing factors. The correlation coefficients (r-values) and p-values were analyzed to determine the strength and statistical significance of these associations. Methods: A correlation analysis was conducted on the haematological parameters. The R-values were calculated to assess the strength and direction of relationships, while the p-values determined the statistical significance. The parameters studied included WBC, HB, HCT, and PLT. The duration of the study was from April 2024 to September 2024. Results: - WBC analysis yielded an R-value of 0.05 and a p-value of 0.034, indicating a positive correlation with statistical significance.- HB analysis showed an r-value of -0.055 and a p-value of 0.604, reflecting a negative correlation that was not statistically significant. - HCT analysis that was also not statistically significant. - PLT analysis produced an R-value of 0.037 and a p-value of 0.727, indicating a negative correlation that was also not statistically significant. Conclusion: The analysis revealed that while the WBCs and AGE showed a statistically significant positive correlation, the other parameters—HB, HCT, and PLT—did not exhibit statistically significant correlations with the variables studied. These findings suggest that the factors investigated have minimal or no meaningful impact on the haematological parameters, warranting further research to identify more significant associations.